Epigenetic Regulation of Methylation in Determining the Fate of Dental Mesenchymal Stem Cells. (22nd September 2022) - Zhang, Hui; Fu, Hong; Fang, Hongzhi; Deng, Qing; Huang, Hao; Hou, Dingyu; Wang, Miaomiao; Yao, Quanzhou; Si, Qiqi; Chen, Rui; Li, Linke; Weng, Jie; et al.
Abstract : Dental mesenchymal stem cells (DMSCs) are crucial in tooth development and periodontal health, and their multipotential differentiation and self-renewal ability play a critical role in tissue engineering and regenerative medicine. Methylation modifications could promote the appropriate biological behavior by postsynthetic modification of DNA or protein and make the organism adapt to developmental and environmental prompts by regulating gene expression without changing the DNA sequence. Methylation modifications involved in DMSC fate include DNA methylation, RNA methylation, and histone modifications, which have been proven to exert a significant effect on the regulation of the fate of DMSCs, such as proliferation, self-renewal, and differentiation potential. Understanding the regulation of methylation modifications on the behavior and the immunoinflammatory responses involved in DMSCs contributes to further study of the mechanism of methylation on tissue regeneration and inflammation. In this review, we briefly summarize the key functions of histone methylation, RNA methylation, and DNA methylation in the differentiation potential and self-renewal of DMSCs as well as the opportunities and challenges for their application in tissue regeneration and disease therapy.